2001
DOI: 10.1161/hc4801.100028
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Catheter Ablation in Infants ≤18 Months Old

Abstract: Participating Members of the Pediatric Catheter Ablation Registry* Background-The objective of this study was to determine the indications, the safety, and the efficacy of pediatric radiofrequency catheter ablation (RFCA) in infants. Methods and Results-Data from the pediatric RFCA registry were reviewed. Between August 1989 and January 1999, 137 infants, defined by age 0 to 1.5 years (median 0.7 years; weight 1.9 to 14.8 kg, median 10 kg), underwent 152 procedures in 27 of 49 registry centers (55%), compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(26 citation statements)
references
References 28 publications
1
22
0
3
Order By: Relevance
“…18 However, several recent studies have shown promising results of RFCA for SVT in young children. 11,14 In the present study, the proportion of patients with AT (18.5%), congenital heart disease and multiple mechanisms of SVT (11.1%), which may increase the difficulties of RFCA, was relatively high. 19,20 Nonetheless, the acute success rate (92.6%), major complication rate (3.7%), and recurrence rate (13%) were all comparable to those in our previous report on the whole pediatric population and in other pediatric reports.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…18 However, several recent studies have shown promising results of RFCA for SVT in young children. 11,14 In the present study, the proportion of patients with AT (18.5%), congenital heart disease and multiple mechanisms of SVT (11.1%), which may increase the difficulties of RFCA, was relatively high. 19,20 Nonetheless, the acute success rate (92.6%), major complication rate (3.7%), and recurrence rate (13%) were all comparable to those in our previous report on the whole pediatric population and in other pediatric reports.…”
Section: Discussionmentioning
confidence: 51%
“…19,20 Nonetheless, the acute success rate (92.6%), major complication rate (3.7%), and recurrence rate (13%) were all comparable to those in our previous report on the whole pediatric population and in other pediatric reports. 1,3,[11][12][13][14]21 The presence of congenital heart disease was not associated with worse outcomes, but this should be interpreted with caution. Most of our patients with congenital heart disease requiring RFCA at such a young age had congenital heart disease other than Ebstein's anomaly, which is notoriously associated with lower success rates and higher recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
“…należy unikać dożylnego podawania werapamilu, ponieważ lek ten może być przyczyną ostrej dekompensacji hemodynamicznej [476]. U małych dzieci powikłania ablacji przezcewnikowej wydają się częstsze, a ponadto istnieją obawy o konsekwencje w fazie dalszego wzrostu po wywołaniu uszkodzeń termoablacyjnych lub krwioablacyjnych w mięśniu sercowym [475,[485][486][487]. Idiopatyczny VT i złożone PVC u dzieci zwykle ustępują samoistnie w ciągu miesięcy do lat [471].…”
Section: Definicje I Epidemiologiaunclassified
“…In a retrospective analysis comparing RFCA in infants <18 months to older children no difference was found, either for success rate, or incidence of major complications. (16) Secondary analysis of patients weighing <15kg, including those older than 18 months, showed an increase in major, but not overall, complication rate. The presence of WPW syndrome associated with syncope when there is a short R-R interval during atrial fi brillation (preexcited R-R interval 250ms) or the anterograde effective refractory period of the AP measured during programmed electrical stimulation is <250ms.…”
Section: Radiofrequency Catheter Ablationmentioning
confidence: 98%